A hybrid mathematical model for an optimal border closure policy during a pandemic - Lazebnik, Teddy; Shami, Labib; Bunimovich-Mendrazitsky, Svetlana (Zielona Góra: Uniwersytet Zielonogórski)
During a global health crisis, a country`s borders are a weak point through which carriers from countries with high morbidity rates can enter, endangering the health of the local community and undermining the authorities` efforts to prevent the spread of the pathogen. Therefore, most countries have adopted some level of border closure policies as one of the first steps in handling pandemics. However, this step involves a significant economic loss, especially for countries that rely on tourism as a source of income.
Keywords: health care; spatio-temporal SIR model; international bio-tourism policy; multi-agent reinforcement learning